Adsorption material composite particles

By employing binder-coated granular carriers with adsorbent layers on natural or artificial sandstone, the invention addresses non-uniformity and cost issues in phosphorus adsorbents, achieving efficient and cost-effective phosphorus recovery.

JP7619695B1Active Publication Date: 2025-01-22竹田 外美
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024083854
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-05-23
Publication Date
2025-01-22
Estimated Expiration
2044-05-23

AI Technical Summary

Technical Problem

Existing phosphorus adsorbents face issues with non-uniform particle sizes, low strength, and high production costs, leading to inefficient phosphorus recovery and increased sludge treatment loads.

Method used

The use of a binder-coated granular carrier with an adsorbent layer, utilizing natural or artificial sandstone as the carrier and cement as the binder, to create uniform, high-strength adsorbent composite particles that enhance phosphorus adsorption efficiency.

Benefits of technology

The solution results in uniformly sized particles with improved adsorption efficiency, reduced resource consumption, and lower production costs, while maintaining strength and ease of regeneration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619695000001
    Figure 0007619695000001
  • Figure 0007619695000002
    Figure 0007619695000002
  • Figure 0007619695000003
    Figure 0007619695000003
Patent Text Reader

Abstract

The object of the present invention is to obtain adsorbent composite particles of a phosphorus component, which effectively utilizes components having an adsorbent function for a phosphorus component, can efficiently uniform the size of the obtained adsorbent composite particles, i.e., can uniform the size of the obtained adsorbent composite particles with a good yield, can eliminate the presence of adsorbents that do not contribute to adsorption inside the particles, is cost-effective, and has sufficient strength. [Solution] Adsorbent composite particles are used, in which a coating layer made of a binder is disposed on the surface of a granular carrier, and an adsorbent is disposed on this coating layer. Natural sand or artificial sand can be used as the granular carrier. A cement selected from Portland cement, mixed cement, and special cement can be used as the binder. A material that adsorbs phosphorus components can be used as the adsorbent.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to adsorbent composite particles, and more particularly to adsorbent composite particles having an adsorbent disposed therein. [Background technology]

[0002] Industrial wastewater, domestic wastewater, agricultural wastewater, livestock wastewater, etc. contain components such as phosphorus that lead to eutrophication. When these flow into rivers, lakes, marshes, and oceans, they cause the outbreak of red tides and the mass outbreak of blue-green algae, etc. Such wastewater is usually treated at sewage treatment plants, etc., but general sewage treatment is not always sufficient to remove nitrogen and phosphorus components, so additional treatment is required to remove these components. Regarding the removal of the nitrogen components, a method can be adopted in which the nitrogen components are subjected to biological treatment and then released into the atmosphere as nitrogen gas. On the other hand, phosphorus components become part of the sludge during biological treatment and are then treated by advanced treatment.

[0003] Phosphorus is an essential component of fertilizer, but the raw material for phosphorus, phosphate rock, is almost entirely imported, and the number of countries that produce it is limited. This raises the risk of problems such as rising prices for phosphate rock and resource depletion. In response to this, there is a demand in Japan to recover and reuse phosphorus components removed from sewage and other sources.

[0004] Methods for removing phosphorus components in sewage treatment include the coagulation and sedimentation method, in which the components are precipitated and removed together with the sludge using coagulants such as metal salts and lime, and the biological treatment method, which utilizes the metabolism of microorganisms to control the anaerobic and aerobic conditions of activated sludge and concentrate and absorb the phosphorus to a high concentration. The phosphorus components concentrated by the biological treatment method can be treated by the crystallization removal phosphorus method, in which the phosphorus components are precipitated together with magnesium ions by crystallization.

[0005] However, the coagulation and sedimentation method requires a large amount of coagulant and a large amount of sludge, and these processes are necessary, while the biological treatment method requires detailed management of the dissolved oxygen concentration and management of the sludge in the final sedimentation tank, and further requires the treatment of sludge with a high phosphorus content. These methods require the recovery of phosphorus from the sludge, which is costly.

[0006] To address these issues, an adsorption method has been proposed in which phosphorus is adsorbed onto an adsorbent. The adsorption method uses a material that has the property of adsorbing phosphorus components, which allows the phosphorus components to be adsorbed and fixed onto the adsorbent and then extracted from sewage, etc. By desorbing the phosphorus components from the adsorbent to which they have been adsorbed and fixed, it is possible to efficiently recover the phosphorus components.

[0007] As an adsorbent for such phosphorus components, a particulate phosphorus adsorbent obtained by calcining nickel hydroxide or coprecipitated hydroxide of nickel and other metals is known (Patent Document 1). However, the adsorption of phosphorus components in these particles occurs only on the surface of the adsorbent, and the inside of the particles does not contribute to the adsorption of phosphorus components.

[0008] In response to this, a porous granular phosphorus adsorbent is known that is made by kneading and granulating phosphorus-adsorbing fine particles, a calcium salt, water, and a highly water-absorbent polymer (Patent Document 2). Because this granular phosphorus adsorbent is porous, not only the phosphorus-adsorbing fine particles on the surface of the adsorbent but also the phosphorus-adsorbing fine particles inside the adsorbent can be effectively used for adsorption of phosphorus components. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2015-202453 A [Patent Document 2] Japanese Patent Application Publication No. 9-141253 Summary of the Invention [Problem to be solved by the invention]

[0010] However, the adsorbent described in Patent Document 2 is a gel hardened material caused by calcium salt, and does not have sufficient strength, so there is a risk of it breaking when used to adsorb phosphorus components. If it breaks, the superabsorbent polymer, which is one of the components, may be one of the factors that increases the COD and BOD, and may be a factor that increases the load on sludge treatment.

[0011] In addition, various phosphorus adsorbents have been proposed, but for the convenience of using the adsorbent, it is required to make it into a granular material. In order to make it into a granular material, a method of adding a binder to granulate the material or crushing a solidified lump to make it into a granular material is known, but in these methods, the size of the obtained granular material is not uniform, so that in order to make the granular material of the required size when used, a larger amount of granular material is required, which results in poor efficiency, i.e., poor yield, and high cost.

[0012] The present invention has been made in consideration of such problems, and aims to obtain adsorbent composite particles of phosphorus components which effectively utilize components having the function of adsorbing phosphorus components, can efficiently make the size of the obtained adsorbent composite particles uniform, i.e., with a good yield, and which eliminates the presence of adsorbents that do not contribute to internal adsorption, are cost-effective, and have sufficient strength. [Means for solving the problem]

[0013] As a result of intensive research, the inventors discovered that the above-mentioned problems can be solved by using an adsorbent having an adsorbent component capable of adsorbing phosphorus components via a binder disposed on the surface of a granular carrier, and thus arrived at the present invention. That is, the present invention has the following features.

[0014] [1] An adsorbent composite particle in which a coating layer made of a binder is disposed on the surface of a granular carrier, and an adsorbent is disposed in this coating layer. [2] The adsorbent composite particle according to [1], wherein the granular carrier is natural sand or artificial sand. [3] The adsorbent composite particle according to [1] or [2], wherein the binder is a cement selected from Portland cement, blended cement, and special cement. [4] The adsorbent composite particle according to [1] or [2], wherein the adsorbent is a material that adsorbs a phosphorus component. Effect of the Invention

[0015] The adsorbent composite particles according to the present invention have a coating layer made of a binder on the surface of a granular carrier, and an adsorbent is disposed on this coating layer, so that the adsorbent is disposed on the surface of the adsorbent composite particles, and most of the adsorbent can be used to adsorb the adsorption target substance such as phosphorus components. Furthermore, since it is easy to uniform the size of the granular carrier, it is easy to uniform the size of the obtained adsorbent composite particles to the desired size. And, since it is easy to obtain adsorbent composite particles of uniform size, it is possible to further improve the adsorption efficiency, and it is possible to suppress the production of adsorbent composite particles of different sizes, which saves resources and eliminates unnecessary costs. In addition, the adsorbent composite particles have a binder disposed on the surface of a granular carrier, and natural sand or artificial sand is used as the granular carrier and cement or the like is used as the binder. Therefore, the adsorbent composite particles are less likely to shatter or crack even when they collide with each other in water, etc., and have sufficient strength to withstand repeated use. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will be described in detail below. The adsorbent composite particles of the present invention (hereinafter sometimes simply referred to as "composite particles") are composite particles in which a coating layer made of a binder is disposed on the surface of a granular carrier, and an adsorbent is disposed in this coating layer.

[0017] The granular carrier is a carrier of granular material as a base material, and is not particularly limited as long as it is granular. The size of the granular carrier is not particularly limited, but it is preferable to adjust the size of the granular carrier to a predetermined range, specifically, within ±30% of the reference particle size, preferably within ±20% of the reference particle size. By adjusting the size within this range, it is possible to adjust the size of the composite particles according to the present invention to a similar range, and it is possible to improve the adsorption efficiency. In addition, as a method for adjusting the size of the granular carrier to the above range, a method using a sieve can be mentioned. By this method, composite particles of the desired size range can be obtained efficiently, i.e., with a good yield. In addition, by making the sizes of the composite particles of the present invention uniform within a similar range, it is possible to improve the adsorption efficiency because sufficient and uniform gaps can be secured between the composite particles, and the phosphorus-containing water can uniformly enter the gaps, so that the space for adsorbing the phosphorus component can be uniformly secured. In other words, it is believed that this is because there is no unevenness in the flow of the phosphorus-containing water, and all the composite particles can obtain similar adsorption conditions.

[0018] Examples of the granular carrier include natural sand and gravel, artificial sand and gravel, metal particles, metal oxide particles, etc., and among these, natural sand and gravel which are easily available and artificial sand and gravel from the viewpoint of waste utilization are preferred. The natural sand and gravel refers to sand, stones, and gravel produced by crushing rocks in nature, such as silica sand, etc. The artificial sand and gravel refers to sand, stones, gravel, etc. produced by artificially crushing rocks that can be collected naturally, or granular material consisting of a glassy or crystalline solidified material obtained by heating waste to 1300°C or higher, pyrolyzing, gasifying, or burning the organic matter in the waste, melting the resulting inorganic matter, etc., residues, and then cooling and solidifying them.

[0019] The binder refers to a material that can be coated on the surface of the granular carrier to form a coating layer, and has a bonding effect of bonding the binder and the adsorbent. Examples of such binders include inorganic binders and organic binders. Examples of the inorganic binders include cement, and examples of the organic binders include organic adhesives. Among these, inorganic binders are preferred from the viewpoint of the possibility of disposing of the resulting composite particles after use. The cement refers to a hydraulic pulverized material containing cement clinker and gypsum (calcium sulfate), and examples of such materials include Portland cement, mixed cement, special cement, etc. Note that the cement clinker refers to alite (tricalcium silicate), belite (dicalcium silicate), aluminate (calcium aluminate), etc. Portland cement is a cement that mainly contains the above-mentioned cement clinker and gypsum, and blended cement refers to cement that has been mixed with these and further contains blast furnace slag, fly ash, silica-based admixtures, etc. Examples of the special cement include white Portland cement, alumina cement, ultra-fast hardening cement, colloidal cement, oil well cement, low heat cement, etc., and among these, cement that does not require heating and undergoes a natural hardening reaction by adding water can be preferably used. Portland cement and blended cement are cements that do not require heating and undergo a natural hardening reaction by adding water.

[0020] The adsorbent refers to a material capable of adsorbing phosphorus components (phosphorus component adsorbent), and examples of such materials include porous alumina (activated alumina), cobalt oxide, and zirconium oxide. The size of the adsorbent is preferably smaller than that of the granular carrier, since it is bonded to the granular carrier via the binder. Specifically, it is preferably 0.1 mm or less. By making it 0.1 mm or less, it is possible to maintain a state in which the adsorption ability is sufficiently maintained, and it is possible to bond a large amount of the adsorbent to the surface of the granular carrier via the binder, thereby achieving a sufficient adsorption effect. The adsorbent may be in a powder or granular form. The powder adsorbent may be used as is, but may be sieved if necessary. In addition, even if the adsorbent is in a granular or powder form, if the particle size of the powder is slightly larger, it may be obtained by crushing and sieving. The phosphorus component refers to an atom or compound containing a phosphorus atom, and examples of such compounds include phosphorus atoms, phosphoric acids such as orthophosphoric acid, phosphates, and organic phosphorus compounds.

[0021] Next, a method for producing the composite particles according to the present invention will be described. First, the binder is brought into a state in which adhesiveness is expressed. Specifically, when cement is used, water is added to the cement to bring about a hardening reaction. Next, the granular carrier is added thereto and mixed by stirring to form a coating layer made of the binder on the surface of the granular carrier. Next, while the bonding property of the binder is maintained, for example, when the binder is cement, before the hardening reaction of the cement is completed, an adsorbent is added and mixed by stirring, so that the adsorbent is bonded to the binder, thereby producing composite particles.

[0022] As a specific example of the manufacturing method, an example using natural sand and gravel as the granular carrier, Portland cement (hereinafter sometimes simply referred to as "cement") as the binder, and activated alumina powder as the adsorbent will be described. First, water is added to the cement and stirred, then natural sand and gravel are added and stirred to coat the surfaces of the natural sand and gravel with the cement. Regarding the amount of water added to cement, if the amount of water is too much, when the natural sand and gravel are added and stirred, the natural sand and gravel particles may be bonded together by the cement. On the other hand, if the amount of water is too little, cement powder that is not wetted by water is produced, making it difficult to cause a sufficient hardening reaction. For these reasons, it is preferable to use an amount of water that does not produce cement powder that is not wetted by water and does not cause the natural sand and gravel particles to be bonded together by the cement. Specifically, although it depends on the amount of natural sand and gravel used, it is preferable that the amount of water be between 40% and 60% by weight. In addition, if the particles of natural sand and gravel are bonded together by cement, the bonds can be released by adding a small amount of dry cement powder and stirring, resulting in a single aggregate of composite particles.

[0023] The amount of cement relative to the natural sand and stone can be set according to the amount of cement you want to coat on the surface of the natural sand and stone. For example, if you want to coat the natural sand and stone with 10% by weight of cement, add an appropriate amount of water to cement equivalent to 10% by weight of the natural sand and stone, stir and mix, then add the natural sand and stone and stir and mix, to obtain independent composite particles (cement amount is 10% by weight of the sand and stone). Note that if the natural sand and stone particles are bonded together by cement and a small amount of cement powder is added to break the bonds, the amount of the small amount of cement powder used to break the bonds is also included in the amount of cement used. The amount of cement coated on the natural sand and stone is preferably 5% by weight or more, and more preferably 7% by weight or more, and is preferably 30% by weight or less, and more preferably 25% by weight or less. By keeping the amount within this range, a sufficient amount of the adsorbent can be disposed in the coating layer, and the resulting composite particles can fully exhibit the effect of adsorbing the phosphorus component.

[0024] The amount of activated alumina used is preferably 3% by weight or more, and more preferably 5% by weight or more, based on the natural sand and gravel used. Also, it is preferably 30% by weight or less, and more preferably 20% by weight or less. By keeping it within this range, all of the activated alumina can be distributed in the coating layer, and the resulting composite particles can fully exhibit the effect of adsorbing phosphorus components.

[0025] The composite particles according to the present invention can regenerate their adsorption ability by desorbing the phosphorus component after adsorption of the phosphorus component, and can be reused. An example of a regeneration method is to bring the material into contact with an aqueous alkali solution such as a 2% by weight to 4% by weight aqueous sodium hydroxide solution to remove the phosphorus components. In addition, when the phosphorus component adsorption effect of the composite particles decreases, the coating layer and adsorbent are removed from the surface of the composite particles using a surface grinding machine or the like, the granular carrier is recovered, and a coating layer made of a binder and an adsorbent are again applied to form composite particles, thereby enabling the granular carrier to be reused. Therefore, only the coating layer and adsorbent removed by the surface grinding machine or the like are discarded, and waste can be significantly reduced. Furthermore, this recycling method is also useful from the viewpoint of energy saving, since it does not require high-temperature heating. Furthermore, even if the composite particles according to the present invention are discarded, the granular carriers that serve as the cores can be returned to nature because they are made of natural or artificial sand and gravel. EXAMPLES

[0026] The present invention will now be described in more detail with reference to examples.

[0027] [Physical Properties] [Measurement of phosphorus concentration in water] Measurement was performed according to the molybdic acid blue method of JIS K-0102. As described later, phosphorus adsorption tests were performed using diluted phosphoric acid (Kishida Chemical Co., Ltd.: primary phosphoric acid, concentration 85% by weight or more) at a specified concentration, so all of the phosphorus contained was phosphorus in the form of phosphorus. For this reason, a decomposition process using ammonium peroxodisulfate, which decomposes organic phosphorus compounds to phosphorus in the form of phosphorus, was not performed.

[0028] [Phosphorus component adsorption test] 100 ml of phosphoric acid-containing liquid adjusted to a predetermined concentration was placed in a 300 ml beaker, and a predetermined weight of an adsorbent sample such as composite particles was added and stirred with a stirrer for a predetermined time. The test liquid was then filtered through a membrane filter (pore size: 0.45 μm), and the phosphorus concentration of the obtained test liquid was measured.

[0029] [Calculation of coating layer thickness] The thickness (Tc) of the coating layer made of the binder was calculated by the following method. The radius of one granular carrier is r, the amount of granular carrier used is W parts by weight, the specific gravity of the granular carrier is ρs, the specific gravity of the binder is ρc, and the amount of binder coated on the granular carrier is N% by weight of the granular carrier. First, the surface area (Ss) of one granular carrier and the volume (Vs) of one granular carrier are: Ss=4πr 2 , Vs=4 / 3×πr 3 , It becomes. The volume (Vw) of the granular carrier of W parts by weight is: Vw=W / ρs From this, the total surface area (Sw) of the granular carrier of W parts by weight is ·Sw={(W / ρs) / (4 / 3×πr 3 )}×4πr 2 , It becomes. Next, the thickness (Tc) of the coating layer applied to the granular carrier is Tc = volume of coating layer / area of ​​coating layer The volume of the coating layer (Tv) is ·Tv={W×(N / 100)} / ρc, It is. Incidentally, when the thickness (Tc) of the coating layer is thin, the area of ​​the coating layer can be regarded as the surface area of ​​the granular carrier, and the volume can be calculated by weight / specific gravity, so the thickness (Tc) of the coating layer can be calculated by the following formula. Tc = volume of coating layer / surface area of ​​granular support =Tv / Sw =[{W×(N / 100)} / ρc] / [{(W / ρs) / (4 / 3×πr 3 )}×4πr2 ] =(N ρs r) / (300ρc)

[0030] [raw materials] Granular activated alumina: Kishida Chemical Co., Ltd.: Reagent (aluminum oxide, activated type (average particle size 5 mm)) Cement: Ordinary Portland cement (product name) manufactured by Taiheiyo Cement Corporation Silica sand: Natural silica sand with varying grain sizes. Two types: average grain size 2mm (grain size 1.7mm-2.4mm) and average grain size 3mm (grain size 2.4mm-3.4mm).

[0031] [Reference example] [Preparation of activated alumina powder and hardened cement granules] The granular activated alumina was crushed in a mortar and sieved to obtain activated alumina powder of 0.1 mm or less. In addition, 40 parts by weight of water was added to 100 parts by weight of the cement, and the mixture was stirred and hardened. If moisture remained, cement powder was added little by little, and if there was any cement powder that was not wet with water, water was added little by little until there was no cement that was not wet with water or any remaining moisture. The hardened product was pulverized in a mortar to obtain hardened cement granules, which were then washed with water to remove unhardened cement components.

[0032] [Verification of phosphorus adsorption performance of activated alumina powder, granular activated alumina, and hardened cement granules] A test solution of 100 ml of 50 ppm phosphoric acid was prepared and placed in a 300 ml beaker. 0.5g of the activated alumina powder, 0.5g of granular activated alumina, and 0.5g of hardened cement particles were added to the test liquid and stirred, and a portion of each test liquid was taken after 5 minutes, 10 minutes, 30 minutes, 1 hour, and 2 hours, and filtered through a membrane filter, and the phosphorus concentration of the recovered test liquid was measured to examine the change in phosphorus concentration in the test liquid as a function of stirring time. The results are shown in Table 1.

[0033] [Table 1]

[0034] As a result, it was found that activated alumina powder, granular activated alumina, and hardened cement granules all have the ability to adsorb phosphorus components, and that adsorption begins early after contact with phosphoric acid, with adsorption completing within about one hour. In addition, when comparing activated alumina powder and granular activated alumina, it was found that even when the same amount was used, the surface area increased by powdering, resulting in a higher adsorption amount.

[0035] [Phosphorus adsorption capacity of granules (coated granules) with a coating layer made of a binder on the surface of a granular carrier] 40% by weight of water was added to the cement and stirred, and 100 parts by weight of silica sand with an average particle size of 2 mm was added and mixed. If there were any parts that were not wetted by the water, water was added little by little until there were no more parts that were not wetted by the water. On the other hand, if the silica sand covered with cement was bonded together, cement powder was added little by little until the bond was broken and the particles became an aggregate of single particles, and no particles consisting only of cement were left. The amount of cement mixed (cement coating amount) of the obtained granules with a coating layer made of cement on the surface of the silica sand (hereinafter referred to as "coated granules") was 10 parts by weight, 20 parts by weight, and 30 parts by weight per 100 parts by weight of silica sand. In addition, hardened cement granules were produced by the above-mentioned method. These hardened cement granules were separated using a sieve, and those with an average particle size of 2 mm were used. The three types of coated granules and hardened cement granules were added to the test liquid (phosphorus concentration 50 ppm) in an amount of 5 ml and stirred, and the phosphorus concentration of the test liquid was measured after 60 minutes and 120 minutes. The results are shown in Table 2 below. The thickness of the coating layer was calculated based on a particle size (r) of 2 mm, a specific gravity of the silica sand (ρs) of 2.65, and a specific gravity of the hardened cement particles (ρc) of 1.8 to 2.2 (a range is shown because this varies depending on the mixture ratio of cement and water).

[0036] [Table 2]

[0037] As a result, it was found that the amount of phosphorus (phosphate) adsorbed was the smallest when the amount of cement coated on the coated granules was 10% by weight. Furthermore, even when the amount of cement coated on the coated granules was increased to 10%, 20%, or 30% by weight, the amount of phosphorus adsorbed did not increase in proportion to the amount of cement coated. In addition, the amount of phosphorus components adsorbed by the hardened cement granules was not significantly different from that of the coated granules when the cement coating amount was 30% by weight. From these, it is considered that the adsorption of phosphorus components (phosphate) occurs near the surface, and there is almost no adsorption inside.

[0038] [Examples 1 to 5] [Production of composite adsorbent particles] Composite particles were produced in the same manner as in the production of the coated granules, except that the activated alumina powder was added at the stage when water was added to the cement and stirred, and then silica sand was added and stirring and mixing began. The amount of silica sand used was 100 parts by weight, and the amount of water added to the cement was initially 40% by weight. The average particle size of the silica sand used was 2 mm and 3 mm. Furthermore, the amount of cement mixed into the composite particles (cement coating amount) was 7 parts by weight and 15 parts by weight per 100 parts by weight of silica sand. The amount of activated alumina powder used was 5 parts by weight and 10 parts by weight per 100 parts by weight of silica sand. The composite particles were added to the test liquid (phosphorus concentration 50 ppm) in an amount of 5 ml or 10 ml and stirred, and the phosphorus concentration of the test liquid was measured after 60 minutes and 120 minutes. The results are shown in Table 3 below. The thickness of the coating layer was calculated assuming a particle size (r) of 2 mm or 3 mm, a specific gravity of the silica sand (ρs) of 2.65, and a specific gravity of the hardened cement particles (ρc) of 1.8 to 2.2.

[0039] [Reference example 1] Granular activated alumina (average particle size 5 mm) was used, 5 ml of the granular activated alumina was added to the test liquid (phosphorus concentration 50 ppm) and stirred, and the phosphorus concentration of the test liquid was measured after 60 minutes and 120 minutes. The results are shown in Table 3 below.

[0040] [Comparative Examples 1 to 4] Next, hardened cement granules were produced by the above-mentioned production method. These hardened cement granules were separated by sieving to produce one with an average particle size of 2 mm (Comparative Example 1) and one with an average particle size of 3 mm (Comparative Example 3). In addition, two types of coated granules were produced using the above method. One had an average silica sand particle size of 2 mm and a cement coating amount of 20% by weight (Comparative Example 2). The other had an average silica sand particle size of 3 mm and a cement coating amount of 10% by weight (Comparative Example 4). 5 ml of each of the particles was added to the test liquid (phosphorus concentration 50 ppm) and stirred, and the phosphorus concentration of the test liquid was measured after 60 minutes and 120 minutes. The results are shown in Table 3 below. The thickness of the coating layer was calculated assuming a particle size (r) of 2 mm or 3 mm, a specific gravity of the silica sand (ρs) of 2.65, and a specific gravity of the hardened cement particles (ρc) of 1.8 to 2.2.

[0041] [Table 3]

[0042] As a result, by comparing composite particles of the same size with particles that do not contain activated alumina powder (cement hardened granules or coated granules) (comparison between Examples 1-2 and Comparative Examples 1-2, and comparison between Examples 3-4 and Comparative Examples 3-4), it was found that even if the amount of cement coating was small, the inclusion of activated alumina powder showed a higher phosphorus component (phosphate) adsorption ability. Furthermore, a comparison between Examples 1 and 2 and Examples 3 and 4 revealed that the greater the amount of activated alumina powder, the higher the phosphorus component (phosphate) adsorption capacity.

[0043] In addition, by comparing Example 1 with Example 3, and Example 2 with Example 4, it was found that the smaller the particle size of the silica sand used, the higher the phosphorus component (phosphate) adsorption capacity. Since the amount (volume) of particles used is the same, the silica sand with the smaller particle size has a larger total surface area. For this reason, even if the same amount of activated alumina powder is used, it is thought that the larger the total surface area, the higher the phosphorus component (phosphate) adsorption capacity. Furthermore, compared with granular activated alumina (Reference Example 1), the composite particles of Examples 1 and 2 exhibited high phosphorus component (phosphate) adsorption capacity, but the composite particles of Examples 3 and 4 exhibited low phosphorus component (phosphate) adsorption capacity. This shows that the average particle size of silica sand affects the phosphorus component (phosphate) adsorption capacity.

[0044] Incidentally, the amount of activated alumina in the composite particles of Example 4 is twice that of the composite particles of Example 5. Meanwhile, the amount of particles used in Example 5 is twice that of Example 4. Therefore, although Examples 4 and 5 have the same amount of activated alumina powder, it was found that Example 5 has a higher phosphorus component (phosphate) adsorption capacity. Since Example 5 uses a larger amount of particles, it has a larger total surface area. Therefore, even if the same amount of activated alumina powder is used, it is considered that the one with a larger total surface area will have a higher phosphorus component (phosphate) adsorption capacity.

Claims

[Claim 1] A method of mixing a binder made of cement selected from Portland cement, blended cement, and special cement with water, Next, a granular carrier made of natural sand or artificial sand is added and stirred and mixed to form a coating layer made of a binder on the surface of the granular carrier. before the hardening reaction of the cement is completed, an adsorbent made of activated alumina is added to bond the adsorbent to the binder to obtain an adsorbent composite particle; A method for producing adsorbent composite particles, in which when the water and the granular carrier are added to the binder and stirred, if the granular carrier coated with a coating layer bonds together, the binder is added in small amounts to eliminate the bonded state, and the adsorbent composite particles become independent particles that are not bonded to each other.

Citation Information

Patent Citations

  • Phosphate ionncontaining liquid treatment

    JP1980031408A

  • Phosphorus removing material, its manufacture and treatment of phosphorus containing water

    JP1994210282A

  • Production of granular dephosphorizing material

    JP1994277504A

  • Adsorbent

    JP2001113165A

  • Adsorbent and method for producing the same

    JP2022138628A